Medical Students’ Reflection on Early Clinical Exposure Experience: A Qualitative Research - Arezou Farajpour; Armin Salehi; Rasam Mashoufi; Ali Bakhshi Bejestani (Strides in Development of Medical Education)
Background: Early clinical exposure to medical curricula can help students understand the social context of medicine and facilitate their transition to the clinical environment.Objectives: The present study was designed and implemented to investigate medical students’ experiences in this regard.Methods: In this qualitative research, 2nd-semester medical students underwent reflection and were asked to respond to open-ended questions in written form after their initial clinical exposure in teaching hospitals. The written responses provided by the students were analyzed using open coding to extract initial codes, subcategories, categories, and themes.Results: The responses of 52 participating students were coded, resulting in the extraction and formation of 252 initial codes, 9 subcategories, 5 categories, and 2 themes.Conclusion: Reflection through early clinical exposure can induce motivation to lay the foundation for developing core competencies, including communication skills, problem-solving, clinical reasoning abilities, personal development, and cultivation of professional identity and professionalism among medical students.